2021
DOI: 10.15441/ceem.20.024
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid albumin ratio as a predictive marker of short-term mortality in patients with acute kidney injury

Abstract: Objective We aimed to investigate uric acid and albumin ratio (UA/A) as a marker of short-term mortality in acute kidney injury (AKI). Both uric acid and albumin are strongly correlated with the development and mortality of AKI. MethodsThe patients hospitalized from May 2019 to September 2019 for AKI were included in this study. The diagnostic odds ratio (DOR), Youden index (J), and the area under a receiver operating characteristic curve (AUROC) determined a cut-off UA/A ratio for mortality. Cox-regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…has been proved to predict short-term mortality in individuals suffering from acute renal damage 12 . Furthermore, UAR predicted the severity of CAD better than the CRP-to-albumin ratio (CAR) in patients with non-ST-elevated myocardial infarction 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been proved to predict short-term mortality in individuals suffering from acute renal damage 12 . Furthermore, UAR predicted the severity of CAD better than the CRP-to-albumin ratio (CAR) in patients with non-ST-elevated myocardial infarction 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been linked to the extent of CAD in ACS patients 11 . Furthermore, UAR has been shown to be a strong predictor of short-term mortality in patients with acute renal failure 12 . To the best of our knowledge, in the literature, there is a lack of studies supporting the association between UAR and the development of NOAF in STEMI patients treated with primary percutaneous coronary intervention (pPCI).…”
Section: Introductionmentioning
confidence: 99%
“…As a new predictive index, the prognostic value of the sUAR has been investigated in patients with STEMI, non-ST segment elevation myocardial infarction, and AKI for predicting mortality. 16 , 30 , 31 Yeter et al found that a sUAR > 1.7 was significantly associated with AKI in critically ill patients. 15 Recently, Faysal et al also demonstrated that sUAR (>1.62) had a greater predictive value for contrast-induced nephropathy, and was superior to serum uric acid and albumin.…”
Section: Discussionmentioning
confidence: 99%
“… 14 The serum uric acid/albumin ratio (sUAR), which is derived from serum uric acid and serum albumin, has been reported as a novel inflammatory marker in predicting AKI, and is associated with mortality in patients with AKI. 15 , 16 Recently, Faysal et al conducted a retrospective study and found that sUAR was an independent predictor of contrast-induced nephropathy. 17 However, the sample size was relatively small and the definition of contrast-induced nephropathy was proved to be not often use in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…17 Similarly, Ozgur et al reported that UAR was associated with short-term mortality in patients with AKI. 18 Cakmak et al noted that UAR was related to the extent of coronary artery disease and predicted clinical outcomes better than the C-reactive protein to albumin ratio and fibrinogen to albumin ratio in non–ST-elevated myocardial infarction patients. 19…”
Section: Introductionmentioning
confidence: 99%